(untitled) (Raparin Journal of Humanities (RJH), 2024)
The aim of this research was to identify the effectiveness of the differentiated education strategy in providing eighth grade students with the foundation of concepts and developing their cognitive curiosity. To achieve the goal of the research, the researcher formulated four main hypotheses, and the researcher used the experimental method for the two equal groups, with the pre and posttest, which requires the presence of two groups, one experimental and the other a control group. The researcher randomly chose two divisions of four divisions to represent the research sample, which is Division (D) to represent the experimental group, and Division (A) to represent the control group, which included (66) female students distributed over the experimental group of (33) students, and the control group with ( 33) female students, and the researcher studied the experimental group according to the strategy (differentiated education), while the researcher studied the control group according to the traditional (ordinary) method. Its final form consisted of (50) paragraphs, of the type of objective tests (multiple choice) and its number was (47) paragraphs, while the essay tests were (3) paragraphs, and The researcher distributed the paragraphs according to Bloom’s cognitive levels (remembering, understanding, application, analysis) and according to their percentage in the specification table. The coefficient of ease, difficulty, discriminatory strength of the paragraphs and the effectiveness of the wrong alternatives were extracted. The researcher also made sure of the validity and reliability of the test by using the Facrotbach coefficient and Crinbach’s alpha formula -20. . The value of the stability coefficient calculated by this equation was (0.89) for the test items. Among the most important findings of the researcher are the following: - There are statistically significant differences at the level of significance (a = 0.05) between the mean scores of the experimental group and the control group in the acquisition of historical concepts test, in favor of the experimental group. In light of the results that the researcher has reached, she recommends the necessity of activating the differentiated education strategy in the educational process.